RESTORING “MEANINGFULNESS” IN HINDU THEOLOGY: CASTE, KARMA AND OVER-SANCTIFICATION - Babu (University of Saint Andrews, Scotland), Kabir (Caderno de Relações Internacionais, 2016)
Hinduism is one of the oldest faiths in the world. Its history is one, which to this day remains a matter of debate and deliberation, due to the lack of historical accounts and archaeological evidences. I believe that by focusing on the loss of sacredness and mean-ing in Hinduism due of Jatization of Varna, it is possible to change the discourse on caste within Hindu theology.